Legal Dynamics of Board of Directors Authority Post - Appointment: An Analysis of Indonesian Corporate Law - Mishra, Diwakar Pratap; Beg, Mirza Juned; Mwangi, Wokabi (Journal of Global Economy, Business and Finance, 2024)
This study examines the legal criteria and processes involved in the empowerment of the Board of Directors in Indonesian Limited Liability Companies, focusing on the procedural aspects post - appointment by the General Meeting of Shareholders. It highlights the regulatory framework governing the authority of the Board of Directors and the role of the Ministry of Law and Human Rights in legitimizing this authority. The research employs a Regulatory Review Methodology and a Normative Juridical approach, analyse the Limited Liability Company Law to elucidate when a Board members authority to legally represent the company commences. The findings emphasize the necessity of a registration receipt from the Ministry for legal representation, thus contributing to a clearer understanding of corporate governance in Indonesia. The purpose of this article is to analyse the legal processes and requirements that validate the authority of the Board of Directors in Indonesian Limited Liability Companies post their appointment, with a specific focus on the role of the Ministry of Law and Human Rights. This article is significant as it provides a comprehensive legal analysis of the authority vested in the Board of Directors of Indonesian Limited Liability Companies, highlighting the critical role of the Ministry of Law and Human Rights in legitimizing this authority, which is vital for corporate governance and legal compliance.